Effects of arginine, glutamine and omega-3 supplementation on the inflammatory response and nutritional status of cancer patients (Research, Society and Development, 2020)
The objective of this study was to review in the literature the effects of supplementation of immunomodulatory nutrients on the nutritional therapy of cancer patients, highlighting impacts on the inflammatory response and nutritional status. The Lilacs, Scielo and PubMed databases were searched, retrieving publications from 2009 to 2019. 158 articles were found in the preliminary search and only 5.7% (n=9) were included. A positive association was found between the use of immunomodulators and an improvement in the overall condition of cancer patients in 100% (n=9) of the studies. Specifically, 55.6% (n=5) observed that supplementation of omega-3 and arginine had positive effects on the inflammatory and nutritional profile. It has been shown that omega-3 and formulas enriched with glutamine, arginine, TCM, carnitine and taurine, contributed to the maintenance of muscle mass in 22.2% (n=2) of the findings, but only in one of them did a reduction in levels of cortisol and PCR. Two other studies found that omega-3 supplementation reduced the risk of postoperative complications, and in one of them, the use of glutamine favored healing processes. It was concluded that the supplementation of arginine, glutamine and omega-3 was effective in improving the response to treatment, malnutrition and inflammatory status in cancer patients.